THE MORAL THEORY OF VALUE; A GIFT LEMMA & HYPOCRISY THEOREM - Adil Ahmad Mughal (International Journal of Contemporary Issues in Social Sciences, 2023)
Aside from the calculating and always troublesome utilitarian ethic, a moral theory of value can better serve as a desirable form of the Rawlsian veil of ignorance analogy on the part of the arbitration of allocation procedures. Kierkegaard suggested a ’moral absolute’ that achieves a ’teleological suspension of the ethical’. This suspension, or the veil of ignorance, can be formulated as a randomization of allocation procedures across agents in a given preference space; such that, a truly self-interested gain remains unpriced in the form of a true gift, that is, a gift without an obligation. Any further than this gift, only, and importantly, the hypocrisy value of unpriced morality is left.